Tadalafil rehabilitation therapy preserves penile size after bilateral nerve sparing radical retropubic prostatectomy - Aydogdu,Ozgu (2011)
OBJECTIVE: To evaluate the change in penile size r bilateral nerve sparing retropubic radical prostatectomy (BNSRRP) and possible effect of Tadalafil. MATERIALS AND METHODS: A total of 65 patients underwent BNSRRP and they were evaluated prospectively for a whole year of follow-up . The patients were randomized to control without rehabilitation (Group 1) or Tadalafil rehabilitation group (Group 2). The patients were evaluated at months 3, 6 and 12 postoperatively for erectile function, penile measurements (flaccid penile length, penile length at maximum erection, penile circumference at flaccid status, and penile circumference at maximum erection), penile abnormalities and general health status. Statistical analysis was performed by Chi-Square test and significance was defined as p value < 0.05. RESULTS: In Group 1 there was significant decrease in penile measurements at month 3 compared to preoperative measurements. There was decrease in all parameters at month 6 compared to month 3 but only the decrease in penile length at maximum erection was significant. There were no significant differences between postoperative months 6 and 12 for all measurements. In Group 2 there was a tendency to decrease in all measurements at month 3 compared to baseline. There was no significant difference for penile measurements between postoperative 3rd and 6th months and between 6th month and the first year. CONCLUSION: Although further large sampled trials are needed to describe the possible positive effect of tadalafil or other PDE5-I's on penile size after BNSRRP, tadalafil rehabilitation is effective in preserving penile size especially in the early postoperative period after BNSRRP.